Counseling and Therapy Recent Developments in Theories and Practices - Fukao, Kenjiro (IntechOpen, 2022)
While the demand for counseling and psychotherapy is increasing in this ever-growing and ever-complicating world, traditional theories and methods are becoming less useful because of the rapid change in people's lifestyles due to technological developments and because of an increase in clients with various ethnic and cultural backgrounds. This volume provides helpful and instructive information on counseling and psychotherapy, including discussions of theoretical innovations and proposals for new practices that transcend ethnic/cultural differences. It also includes chapters addressing the status of counseling services in African states under the COVID-19 pandemic.